(3GdefgL aj GdJOGhi ef Ufha GdCeQGV hGdTcGhis - (3CHh SYjO Hf EHQGgje GdeZQHj GdYdGFjs
(3ChdgG (B:s
(3Ef Chd eG GaJJM Hg GdcJGH hdeGcGfJ GdCOhjI hGdCZPjI eGOI JMaX UMI GdEfSGf ,hgHhdi deOGhGI CSbGe GdCHOGf ,cGf ef GdhGLH Ydi GdWHjH eYQag eGgjJgG hCeRLJgG s
(3BNQgG (B:s
(3ZdJGf gh GdLOhGQ PcQ ai Mj Je GdcJGH GdeHGQc HMeO Gddg JYGdi s
(3fSNI QGHYIs
(3cJH YdjgG YfhGf (B:(3GdefLM ai GdeaQOGJs
(3deLghds
(3hdcffG hLOfG CfgG JJab eY GdfSNI GdSGHbI HOAkG hNGJeI s
(3ceG Cfg cJH Ydi fSNI CNQi ai faS GdecJHI GdJi UhQJ YfgG gPg GdfSNI ecJHI eLdS ThGQi Cf GdcJGH dCHf SYjO GdeZQHi hjHOh Cf gPG GdcJGH YQa Hg s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs